Income inequality and public policy in Argentina (1996-2014). (2017)
This article analyses the evolution of income inequality in Argentina through the decomposition of the Gini coefficient by income sources. The dynamic analysis allows for simultaneous changes in participation and concentration of different income sources to be understood. The time periods that are the object of the analysiscontrast diverse macroeconomic contexts, labour market institutions and social protection policies that were implemented. The results indicate that labour income is the main driver of distributive dynamics while retirement income has also played an important role. We also find that the evolution of income distribution in Argentina is closely related to labour market institutions and macroeconomics.